2008
DOI: 10.1016/j.ijgo.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intraepithelial neoplasia recurrence after conization in HIV‐positive and HIV‐negative women

Abstract: Recurrence rate of CIN in HIV-positive women was higher than in HIV-negative women. The factors associated with recurrence were HIV infection, glandular involvement, and positive margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…24 A Brazilian study demonstrated that immunosuppressed women had a higher risk of lesion recurrence compared to women with a CD4 T-lymphocyte count > 200 cells/mm 3 . 25 In our study, there was significant association between HIV-related immunodeficiency measured by CD4 T-lymphocyte count, and the presence of CIN. This association remained statistically relevant even after controlling for HPV detection.…”
Section: Discussionsupporting
confidence: 49%
“…24 A Brazilian study demonstrated that immunosuppressed women had a higher risk of lesion recurrence compared to women with a CD4 T-lymphocyte count > 200 cells/mm 3 . 25 In our study, there was significant association between HIV-related immunodeficiency measured by CD4 T-lymphocyte count, and the presence of CIN. This association remained statistically relevant even after controlling for HPV detection.…”
Section: Discussionsupporting
confidence: 49%
“… positive surgical margins with LEEP or cervical conization (present in >40% of HIV+ women) (Boardman et al 1999;Gilles et al 2005;Lima et al 2009).  glandular involvement (Lima et al 2009).…”
Section: Other Resources Neededmentioning
confidence: 99%
“… glandular involvement (Lima et al 2009).  greater immunosuppression (Holcomb et al 1999;Shah et al 2008)  lack of suppressive ART (Robinson et al 2001).…”
Section: Other Resources Neededmentioning
confidence: 99%
“…In this study, persistent CIN was noted in 46% of HIV-positive women and 33% of HIV-negative women 6 months after their initial treatment by cryotherapy, LEEP, knife conization, laser ablation, or laser conization [38]. More recently, Lima and colleagues [39] reported on a cohort of 98 HIV-positive and 120 HIV-negative Brazilian women. In their study, recurrence rates of CIN were 33% among HIV-positive women and 8.4% among HIV-negative women completing 24 months of follow-up after LEEP ( P <0.01) [39].…”
Section: Treatment Options For Cervical Precancermentioning
confidence: 97%
“…More recently, Lima and colleagues [39] reported on a cohort of 98 HIV-positive and 120 HIV-negative Brazilian women. In their study, recurrence rates of CIN were 33% among HIV-positive women and 8.4% among HIV-negative women completing 24 months of follow-up after LEEP ( P <0.01) [39]. Treatment failure may also be associated with immunosuppression [40, 41], endocervical disease [40], positive margins, and HPV infection [42].…”
Section: Treatment Options For Cervical Precancermentioning
confidence: 99%